Growth Performance and Survival of Larvae of Ompok pabda Produced from Vitamin E Treated Female Broodfish - Mollah, MFA; Sarowar, MN (Progressive Agriculture, 2013)
An experiment was conducted to observe growth performance and survival of the larvae produced from the brood fish of Ompok pabda treated with 4 dietary levels of vitamin E for 90 days viz. 0 (served as control), 50, 100 and 150mg vitamin E/kg feed under 4 treatments i.e. treatment T1, T2, T3 and T4. After the feeding trials, the brood fish were induced to breed with equal dose of PG extract i.e. 12 and 18mg/kg body weight for male and female respectively and subsequently larvae were produced. The experiment was started with 5 days-old larvae having an average weight and length of 21.4 ± 8.6 mg and 13.8 ± 2.49 mm respectively in 16 bowls of 10l capacity divided into 4 treatments corresponding to the broods fish having 3 replications each with 100 larvae in each bowl i.e. 10 larvae per liter. After rearing for 28 days with live-food tubificid worms the highest growth rate in terms of weight (609.13 ± 15.20 mg) and length (86.70 ± 1.84 mm), gain in weight (587.78 ± 15.27 mg) and length (72.98 ± 1.81 mm), specific growth rate (30.36 ± 0.12%), health condition (16.63 ± 0.69 mg/mm) and survival (83.25 ± 2.87) were showed by the larvae produced from brood fish fed with 100 mg vitamin E/kg feed (treatment T3) while poorest was observed by the larvae produced from brood fish fed 150 mg vitamin E/kg feed. The results imply that inclusion of 100mg vitamin E/kg feed in the diet of O. pabda brood fish is best for enhancing growth and survival of larvae indicating that vitamin E has a positive impact. The results also suggest that inclusion of higher level of vitamin E in the diet exerts an antagonistic effect on the produced larvae. DOI: http://dx.doi.org/10.3329/pa.v20i1-2.16864 Progress. Agric. 20(1 & 2): 125 132, 2009